Alpha-2B Adrenergic Receptor Mediated Hemodynamic Profile of Etomidate - Creagh, Osmar; Torres, Héctor; Rodríguez, Normidaris; Gatica, Sebastián Rodrigo (Puerto Rico Health Sciences Journal, 2010)
Etomidate has been used since 1972 as an inductor and maintaining anesthesia. There are multiple mechanisms that account for the biologic effects of Etomidate. One of the most prominent features of this drug is to provide anesthesia without gross changes in hemodynamic parameters. This feature allows using Etomidate in patients with considerable cardiopulmonary compromise avoiding the characteristic hypotension produced by other anesthetics. A mechanism that provide basis for its cardiovascular stability is the capacity to bind and stimulate peripheral alpha-2B adrenergic receptors with a subsequent vasoconstriction. Alterations in the function or number of these receptors may account for abnormal responses during Etomidate induction.